The Barber Sdn. Bhd. / Muhammad Hazim Mahmud, Zulhafizi Juaser and Azim Muzani - Mahmud, Muhammad Hazim; Juaser, Zulhafizi; Muzani, Azim (2018)
The team is inventing EZstyle, that is the first hair styler technology in the world. Nowadays, a lot of people keep busy in their life unable them to go to saloon to have hair treatment and styling their hair. This product is suitable for adult both male and female.